Modeling and analysis of radionuclide structure of high active waste from VVER-440 reactors spent nuclear fuel reprocessed with Production Association "Mayak" technology - P. M. Rusinko; L. L. Litvinsky (Ядерна фізика та енергетика)
Results of modeling of radionuclide structure of high active waste from VVER-440 reactors spent nuclear fuel reprocessed with PA "Mayak" technology are presented in the article for different values of fuel burnup. The contribution of different radionuclides in this waste specific activity at different periods from 23 till 108 years is analyzed. The basic fission products and actinides are determined, for which contribution to total specific activity of such a waste is essential.